EXPLORING THE REACTIVITY AND INTERACTIONS OF A POLY(FLUORENE-CO-TETRAZINE)-CONJUGATED POLYMER WITH SWNTS - Ly, Alexandra (My University, 2023)
Conjugated tetrazine-containing polymers that undergo Inverse Electron Demand Diels-Alder (IEDDA) reactions with trans-cyclooctenes are interesting not only for their intrinsic optoelectronic properties, but also their interactions with π-conjugated surfaces. Here, we prepared a series of poly(fluorene-co-tetrazine) polymers and carried out IEDDA reactions to decorate them with hydroxyl, hexadecyl, or triethylene glycol side chains. The polymers were investigated pre- and post-IEDDA coupling in terms of their ability to disperse single-walled carbon nanotubes (SWNTs) in organic solvent. It was found that polymer molecular weight, side chain structure, and degree of conjugation all impacted the quality of SWNT dispersions. While the starting poly(fluorene-co-tetrazine) polymer produced concentrated dispersions, the post-IEDDA polymer containing dihydropyridazine groups did not produce dispersions of equal concentration. However, upon oxidation to the fully aromatic pyridazines, the polymers regained their ability to form concentrated dispersions. Furthermore, the post-IEDDA polymers exhibited increased selectivity toward metallic SWNTs relative to the starting polymer. In addition, due to the efficiency of the IEDDA reaction, it was possible to perform modification of the polymer-SWNT dispersion formed with poly(fluorene-co-tetrazine) to modify the polymer structure while on the SWNT surface. Overall, this work demonstrates the first use of reactive polytetrazines to disperse SWNTs and to rapidly modify the solubility of polymer-nanotube complexes.
Keywords: Tetrazine; Conjugated polymers; SWNT; Carbon nanotube